Analisis Supply Chain Management Menggunakan Metode Value Stream Mapping (VSM) (Studi Kasus : Kinara Bakeri Kota Binjai) - Br Sembiring, Latifah Hanum; Chandra, Riny; Safrizal, Safrizal (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to find out how the flow of supply chain management in Kinara Bakeri, Binjai city, whether there is waste or not, the method used in this study is a qualitative method using VSM (value stream mapping) measuring instruments. The object in this study is Kinara Bakeri in the city of Binjai which has been established for 29 years. Data collection methods through interviews, direct observation and documentation. The results of this study found a total lead time value of 671 minutes, a waiting time value of 145 minutes, with a VA (Value Added) value of 181 minutes and an NVA (Non Value Added) value of 353 minutes and a PCE (process cycle efficiency) value of 26.9%, which means kinara Bakeri's supply chain management is included in the un-lean category because the PCE value is less than 30%.Â